Developing a Metaverse-Based Learning Environment for High School Students in Ukraine: A Survey-Based Analysis - Kovalenko, Olena; Shevchenko, Dmytro; Melnyk, Iryna (CV TOPAZART, 2025)
The metaverse—an interconnected network of immersive, persistent, and interactive virtual worlds—has emerged as a promising paradigm in educational technology. By integrating virtual reality (VR), augmented reality (AR), and Web3-enabled platforms, the metaverse has the potential to reshape secondary education through deeply engaging, experiential, and context-rich learning experiences. This paper presents the findings of a survey-based study conducted with a sample of 120 high school students and 35 educators across various regions of Ukraine. The survey aimed to assess awareness, perceptions, and readiness for metaverse integration in the high school curriculum, as well as to identify potential benefits and barriers. Results reveal strong enthusiasm for metaverse adoption, with 78% of students and 65% of teachers expressing high interest in its educational use. The most commonly cited benefits include heightened student engagement, real-time collaborative opportunities, and the enhancement of STEM and digital literacy skills. However, significant challenges remain, particularly related to high hardware costs, inadequate internet infrastructure, limited teacher training, and concerns regarding data privacy. The paper concludes with strategic recommendations for phased implementation, teacher capacity building, and the development of clear policies to ensure equitable and ethical use of metaverse technologies in Ukrainian high schools.